Tinjauan Hukum Pembagian Hak Waris Istri dan Perkawinan Poligami di Tinjau dari Kompilasi Hukum Islam - Syaichul Mubarok; Farhan Asyhadi; Muhammad Abbas (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Polygamous marriage in Indonesia continues to be a very active legal issue, both in normative, social, and legal aspects. In the existing legal context, polygamy is considered fundamental based on Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law, but only with strict conditions and procedures, namely the need for court approval and written permission from the first wife. If polygamy meets the established formal and material requirements, then the second, third, or fourth wife has legal status and is included in the legal consequences, including issues of property and inheritance rights. The objective of this study is to examine the impact of polygamous marriage on the inheritance rights of the second, third, and fourth wives as determined by Regulation Number 1 of 1974 and the Compilation of Islamic Law. The approach used in this study is a normative juridical analysis with literature analysis. The results of the study indicate that each wife has the right to receive inheritance according to Islamic law, but only regarding joint property acquired during the marriage bond, the second, third, and fourth wives do not have rights to the property obtained before they were married. Therefore, the validity and registration of polygamous marriages have a major impact on the recognition and protection of inheritance rights for each wife.